2015
DOI: 10.1051/0004-6361/201424991
|View full text |Cite
|
Sign up to set email alerts
|

SN2014J gamma rays from the56Ni decay chain

Abstract: Context. The detection and measurement of gamma-ray lines from the decay chain of 56 Ni provides unique information about the explosion in supernovae. SN2014J at 3.3 Mpc is a sufficiently-nearby supernova of type Ia so that such measurements have been feasible with the gamma-ray spectrometer SPI on ESA's INTEGRAL gamma-ray observatory. Aims. The 56 Ni freshly produced in the supernova is understood to power the optical light curve, because it emits gamma rays upon its radioactive decay first to 56 Co and the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
105
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(118 citation statements)
references
References 24 publications
12
105
1
Order By: Relevance
“…Churazov et al (2014) derive 56 Ni = 0.62 ± 0.13 M . Diehl et al (2015) find a slightly lower mass of M56 Ni = 0.56 ± 0.10 M .…”
Section: Test With Well-observed Sne Iamentioning
confidence: 76%
See 1 more Smart Citation
“…Churazov et al (2014) derive 56 Ni = 0.62 ± 0.13 M . Diehl et al (2015) find a slightly lower mass of M56 Ni = 0.56 ± 0.10 M .…”
Section: Test With Well-observed Sne Iamentioning
confidence: 76%
“…Since t 2 is independent of reddening, we can use the derived correlation to determine the peak luminosity and estimate the 56 Ni mass for heavily reddened SNe Ia. We tested this relation on SN 2014J, which has a direct γ-ray detection from the 56 Ni → 56 Co decay chain (Churazov et al 2014;Diehl et al 2015). Using the best fit relation for the reddening-free sample, we obtain M56 Ni = 0.64 ± 0.15 M for a t 2 = 31.99 ± 1.15 days and a rise time of 19 days.…”
Section: Test With Well-observed Sne Iamentioning
confidence: 99%
“…INTEGRAL could detect the long awaited gamma-ray signatures of the thermonuclear runaway, through the early emission from the decay of 56 Ni (mean lifetime τ 8.8 days) about 20 days after the explosion, and the main gamma-ray lines at 847, 1238, and 511 keV from the decay of 56 Co (τ 111 days). These data suggested either a surface explosion or some unusual morphology of the runaway [44,45,53,54,76], either case in stark contrast to the conventional Chandrasekhar model. Clearly, the glimpse offered by SN2014J observations underlines the importance of gamma-ray line diagnostics in these systems and emphasize that more and better observations hold the key to a deeper understanding of how the thermonuclear explosion of a white dwarf star unfolds.…”
Section: Antimatter and Wimp Dark Mattermentioning
confidence: 83%
“…4 in Ref. [54], red data points) are compared to a family of candidate models [137]. A simulation of the response to a time evolution such as in the W7 model [99] shows that the sensitivity improvement by e-ASTROGAM (blue points) will lead to breakthrough science.…”
Section: Antimatter and Wimp Dark Mattermentioning
confidence: 99%
“…The general results from INTEGRAL, which detected the 847 and 1238 keV γ -ray lines of radioactive 56 Co (Churazov et al 2014(Churazov et al , 2015Diehl et al 2014Diehl et al , 2015, showed that the general nickel distribution was stratified with a total 56 Ni mass of ∼0.5 M . Due to the low signal to noise, there is some ambiguity about just how to interpret the results, that is, whether the γ -rays favour symmetric nickel distributions (Churazov et al 2014(Churazov et al , 2015 or whether the lines are significantly Doppler-broadened asymmetric ones (Diehl et al 2014(Diehl et al , 2015. We are not terribly sensitive to small asymmetries, and therefore we cannot distinguish between these different interpretations.…”
Section: O M Pa R I S O N W I T H Smentioning
confidence: 99%